2010
DOI: 10.1186/1744-9081-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local anesthesia of the cerebellum on classical fear conditioning in goldfish

Abstract: BackgroundBesides the amygdala, of which emotion roles have been intensively studied, the cerebellum has also been demonstrated to play a critical role in simple classical fear conditioning in both mammals and fishes. In the present study, we examined the effect of local administration of the anesthetic agent lidocaine into the cerebellum on fear-related, classical heart-rate conditioning in goldfish.MethodsThe effects of microinjection of the anesthetic agent lidocaine into the cerebellum on fear conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
3
25
1
Order By: Relevance
“…Lastly, the authors reported that the observation of normal swimming activity or obstacle avoidance indicated that cerebellum lesions did not produce any observable motor deficit, and the lesions did not interfere with the occurrence of unconditioned motor or emotional responses. Rodriguez et al (2005), Yoshida and Hirano (2010), and Gómez et al (2010) reached the same conclusion; the functional involvement of the teleost's cerebellum in learning and memory is very similar to that of mammals. Subsequently, the authors suggest that the cognitive and emotional functions of the cerebellum may have evolved early in vertebrate evolution, having been conserved along the phylogenetic history of the extant vertebrate groups.…”
Section: Associative Learningsupporting
confidence: 58%
See 1 more Smart Citation
“…Lastly, the authors reported that the observation of normal swimming activity or obstacle avoidance indicated that cerebellum lesions did not produce any observable motor deficit, and the lesions did not interfere with the occurrence of unconditioned motor or emotional responses. Rodriguez et al (2005), Yoshida and Hirano (2010), and Gómez et al (2010) reached the same conclusion; the functional involvement of the teleost's cerebellum in learning and memory is very similar to that of mammals. Subsequently, the authors suggest that the cognitive and emotional functions of the cerebellum may have evolved early in vertebrate evolution, having been conserved along the phylogenetic history of the extant vertebrate groups.…”
Section: Associative Learningsupporting
confidence: 58%
“…Contrasting the lack of effects of telencephalic ablations, research conducted by Gómez, Durán, Salas, and Rodríguez (2010), Yoshida and Hirano (2010), and Rodríguez et al (2005), exemplifies cumulated evidence supporting the notion that teleost's cerebellum is essential for the classical conditioning of several types of behavior (in the same way that it is for mammals). Rodriguez et (2010) analyzed the involvement of the cerebellum in the classical conditioning of motor and emotional responses and on spatial cognition.…”
Section: Associative Learningmentioning
confidence: 99%
“…Therefore, these might be homologues of the mammalian pontine nucleus. Some of these relay points will convey higher cognitive information between the telencephalon and cerebellum, and indeed, fish cerebellum participates in fear conditioning (Yoshida & Hirano ) or spatial cognition (Durán et al . ).…”
Section: Cerebellummentioning
confidence: 99%
“…Therefore, these might be homologues of the mammalian pontine nucleus. Some of these relay points will convey higher cognitive information between the telencephalon and cerebellum, and indeed, fish cerebellum participates in fear conditioning (Yoshida & Hirano 2010) or spatial cognition (Dur an et al 2014). Further investigations are required to determine whether telencephalo-cerebellar pathways in teleosts are primordial cerebral cortex-cerebrocerebellum circuits and whether the teleost cerebellum participates in various cognitive functions.…”
Section: Cerebellummentioning
confidence: 99%
“…Fish learn to avoid electric shocks usually in one or a few trials (e.g. Yoshida and Hirano, 2010). This avoidance behaviour persists for up to 3 days (Dunlop et al, 2006), but after 3 days of food deprivation fish will risk entering the shock zone to obtain food (Millsopp and Laming, 2008).…”
Section: Pain In Fishmentioning
confidence: 99%